Genom Mitokondria (MITOCHONDRIAL GENOME) - Wandiya, I Nengah (Jurnal Veteriner; Vol 2 No 4 (2001), 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: mitochondria, mtDNA